Bentuk dan Tingkat Partisipasi Masyarakat pada Program Penanganan Permukiman Kumuh - Fathiyya Nabila; Zahrul Fuady; Fahmi Aulia (Universitas Syiah Kuala, 2023)
Community participation plays an important role in supporting the implementation of the slum settlement program. Gampong Seutui, Baiturrahman District, Banda Aceh City is a priority location in the handling of slum settlements carried out by KOTAKU (City Without Slums). The slum settlement program requires community participation to have a more positive influence on development. Therefore, it is very interesting to know how the level of participation of the people of Gampong Seutui is in the implementation of the slum management program. The analysis was carried out by processing the questionnaire data using the scoring and weighting method. The results of the study show that the form of community participation is divided into the form of participation of thoughts, energy, property as well as skills and abilities. The dominant form of thought participation is giving opinions and suggestions at the deliberations as much as 42%, the dominant form of energy participation is attending the deliberations as much as 69%, the dominant form of property participation is giving food and money donations 39%, and the forms of participation in skills and proficiency that are carried out dominantly are as much as 8%. The level of community participation occupies the tokenism participation rate of 59%. tokenism is divided into 3, namely informing by 27%, consultation by 30%, and placation by 2%. The level of participation at the tokenism level is indicated by the community participating in providing opinions/suggestions but there is no guarantee that opinions, proposals will be considered, the community is not much involved in decision making, so that the majority of the community only runs a program/activity from providing information obtained from socialization or from one-way media.